Early, Contemporary, Recent: Discussions on Realist Narratives - Fořt, Bohumil (Bohemica Olomucensia, 2018)
The study shows some of the topics and ideas present in the early discussions of literary realism from the beginning to the present day. Although these ideas are articulated in different ways, in different contexts and with different purposes, it is possible to show nuclear leitmotifs which can be interconnected with modern theoretical inquiry and its concepts.
Keywords: realism; reality; truth; realist illusion; reality effect; morality